Mobbing in the Health service (Legal, social and therapeutic aspects) - Sadowska, Ludwika; Kańczuła, Sławomir (European Journal of Clinical and Experimental Medicine, 2010)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The article deals with the present-day causes of the existence within the health care personal of psychological harassment called the mobbing. This phenomenon was described with reference to crisis situations. At the same time, it presents the methods of its diagnosis and preventing of it in the light of the Constitution of the Republic of Poland, the binding labor law and of the Code of medical ethics. The authors bring up also the role and the tasks of the all-Polish anti-mobbing Association (OSA) in our country.